2022
DOI: 10.1186/s12887-022-03381-4
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center, pragmatic, effectiveness-implementation (hybrid I) cluster randomized controlled trial to evaluate a child-oriented goal-setting approach in paediatric rehabilitation (the ENGAGE approach): a study protocol

Abstract: Background Child-oriented goal-setting in pediatric rehabilitation may improve child motivation, engagement in therapy, child outcomes related to therapy, and service delivery efficiency. The primary objective of this trial is to determine the effectiveness of a principles-driven, child-focused approach to goal-setting, Enhancing Child Engagement in Goal-Setting (ENGAGE), on pediatric rehabilitation outcomes compared to usual practice. The three secondary objectives are to 1) compare costs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…Knowing that pain can negatively impact QOL, it should also be noted that reported pain severity values for CMD that attended PACE were reduced. The values of 2.92 and 2.15 for the 2010-2011 and 2011-2012 years, respectively, are lower than those reported for similar children [43,44].…”
Section: Discussioncontrasting
confidence: 65%
“…Knowing that pain can negatively impact QOL, it should also be noted that reported pain severity values for CMD that attended PACE were reduced. The values of 2.92 and 2.15 for the 2010-2011 and 2011-2012 years, respectively, are lower than those reported for similar children [43,44].…”
Section: Discussioncontrasting
confidence: 65%
“…Finally, while using parent reported measures, it is observed that parents may either overestimate or underestimate the impact of pain in children due to the parent’s personal characteristics and contextual factors [ 55 ]. This may lead to a mismatch between the clinician’s, child’s, and parent’s perspective on creating meaningful and appropriate goals [ 55 , 56 ]. Given that children above the age of 8 can reliably use self-report measures, [ 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…9, 11,14 and 17). The inclusion of activities specifically selected by children provides a strong framework for creating collaborative goal setting between the child, rehabilitation professional, family, and other professionals thereby facilitating family-centered care [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, creating goals that are valued by the child and are considered meaningful is critical to obtain improvements in function. [42][43][44] In contrast to PVSQ and DHI-PC, Item 7 of the PDI provides an opportunity to children to identify their activity of choice.…”
Section: Face and Content Validitymentioning
confidence: 99%